Effects of periodontal disease prediction system on oral hygiene motivation in patients with periodontitis: a prospective randomized controlled clinical study - Gunpinar, Sadiye; Ezer, Uemran Gundogdu; Gonulay, Seda; Tasmektepligil, A. Alper; Gunpinar, Erkan (SPRINGER HEIDELBERG, 2025)
Aim The aim of this study is to enhance and maintain individual patients' oral hygiene motivation using a computer-based visualization program entitled as Periodontal Disease Prediction (PDP). Materials and methods Patients were randomly assigned to three groups: (a) conventional method group (CM, n = 40), (b) Three-dimensional animation (3DA, n = 40), and (c) PDP interaction (n = 40). A total of 120 patients (60 females, 60 males; aged 30-60 years) diagnosed with Stage III Grade B periodontitis and poor oral hygiene (OHI-S > 3) were included. Baseline data of all patients including probing depth (PD), papillary bleeding index (PBI), bleeding on probing (BOP), Rustogi modified Navy Plaque Index (RMNPI) were recorded, and all patients received the necessary scaling and root planing. All groups were examined periodontally at 3, 6, and 12 months after initial periodontal treatment. Results At all evaluated time periods, PDP group demonstrated a significantly greater reduction in PBI and RMNPI, particularly associated with interproximal surface cleaning, compared to the other groups (p 0.05). Furthermore, PDP group showed significantly greater reduction in BOP compared to the other groups, but this was only observed at the 3-month reevaluation. There were no significant differences among the groups regarding PD and pocket closure (PD >= 4 mm %) (p > 0.05). Conclusion Informing patients about their probable periodontal breakdown using the PDP system, which simulates their individual condition, can enhance their oral hygiene motivation, particularly in maintaining effective interface cleaning. This approach may also help reduce the risk of periodontal disease recurrence.
Keywords: Bleeding on probing; Oral hygiene motivation; Periodontitis; Three-dimensional animation; HEALTH EDUCATIONAL-PROGRAM; 11TH EUROPEAN WORKSHOP; RISK-FACTOR; BEHAVIOR; INTERVENTION; INSTRUCTION; PLAQUE; CARE; PREVENTION; GINGIVITIS; Dentistry, Oral Surgery & Medicine